PELATIHAN MICROSOFT EXCEL UNTUK PERSIAPAN SELEKSI MASUK KERJA DI LEMBAGA KEUANGAN - Ani Nuraini; Lailatul Maziyah Wildan Mufaridho; Dewi Susanawati; Paiz Jalaludin; Muslimin (Jurnal Pengabdian Masyarakat (Bisma), 2025)
Microsoft Excel training is an effective way to equip students with relevant initiative practical skills, particularly for job selection, particularly in financial institutions that require administrative and data analysis skills. This community service activity was conducted at the Al Hasanah Islamic Boarding School in Pamulang with the aim of enhancing students' proficiency in using Microsoft Excel as a tool to support future workplace productivity. The implementation method consisted of three stages: preparation, execution, and evaluation. The preparation stage involved identifying students' needs and developing training modules. During the execution stage, the training materials covered basic Excel functions, creating simple financial reports, and utilizing formulas and logical functions relevant to the financial sector. Evaluation was conducted by distributing questionnaires to participants to measure satisfaction and training effectiveness. The results demonstrated high enthusiasm from participants and an improvement in their understanding of Microsoft Excel, particularly its application in the workplace. Thus, this training positively contributed to preparing students for the challenges of the job market, especially in the financial field. Keywords: